2007
DOI: 10.1590/s0100-879x2007000100015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of etoricoxib and indomethacin for the treatment of experimental periodontitis in rats

Abstract: We investigated the effect of etoricoxib, a selective cyclooxygenase-2 inhibitor, and indomethacin, a non-selective cyclooxygenase inhibitor, on experimental periodontitis, and compared their gastrointestinal side effects. A ligature was placed around the second upper left molars of female Wistar rats (160 to 200 g). Animals (6 per group) were treated daily with oral doses of 3 or 9 mg/kg etoricoxib, 5 mg/kg indomethacin, or 0.2 mL saline, starting 5 days after the induction of periodontitis, when bone resorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
3
12
2
1
Order By: Relevance
“…Thus, when treatment is started later, bone loss is no longer affected. In contrast to what has been suggested by other studies , we found that selective inhibition of COX‐2 has a limitation in the treatment of alveolar bone loss induced by periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, when treatment is started later, bone loss is no longer affected. In contrast to what has been suggested by other studies , we found that selective inhibition of COX‐2 has a limitation in the treatment of alveolar bone loss induced by periodontitis.…”
Section: Discussioncontrasting
confidence: 99%
“…In the same dose as that used in the present study, it can control hiperalgesia 26 and reduce bone loss in periodontal disease 1 , in rats. In 2008, the Brazilian Agency of Sanitary Surveillance (ANVISA) suspended commercialization of 120 mg pills of etoricoxib, but allowed the sale of 60 and 90 mg pills provided the retention of medical prescription and inclusion of adverse effects warning in the bulla were done.…”
Section: Discussionmentioning
confidence: 76%
“…Under anesthesia with sodium pentobarbital, 36 adult male Sprague–Dawley rats were treated as follows: silk ligatures (no. 3‐0; Golden Circle Medical Limited Corporation, Shanghai, China) were tied around the cervixes of the right second maxillary molar, while the contralateral tooth was untreated (19). Subsequently, the animals were randomly divided into three groups (12 animals per group).…”
mentioning
confidence: 99%